Rekonstruksi Pengawasan Negara terhadap BUMN dalam UU No. 1 Tahun 2025: Kritik atas Model Kelembagaan BPI Danantara - Angelica Jasmine Margareta, Julia (Zaaken: Journal of Civil and Business Law, 2026)
State supervision over State-Owned Enterprises (SOEs) in Indonesia has undergone significant transformation following the enactment of Law Number 1 of 2025, particularly through the establishment of the Daya Anagata Nusantara Investment Management Agency (BPI Danantara). This reform raises critical legal issues concerning the clarity of authority, oversight structure, and institutional accountability. This study aims to examine the state supervision mechanism under the new regulatory framework and to propose an ideal supervisory model. Employing a normative juridical method with statutory and conceptual approaches, the study finds that the dual holding structure and the inter-SOE monitoring mechanism introduced by BPI Danantara create overlapping authorities, role conflicts, and unclear lines of accountability, potentially undermining state control and principles of good corporate governance. Therefore, an institutional reconstruction is necessary, including the elimination of the operational holding function and the reallocation of supervisory authority to the President and the Minister of SOEs in a proportional manner. This study contributes to the development of state supervision theory in public corporate governance and offers normative recommendations for reforming SOE governance in Indonesia.